PENGATURAN PENYELENGGARAAN REKLAME DALAM PERATURAN DAERAH KOTA DENPASAR NOMOR 29 TAHUN 2001 TENTANG PAJAK REKLAME - I Made Ksema Dharma Yogata; I Wayan Parsa; I Ketut Suardita (Kertha Negara : Journal Ilmu Hukum, 2013)
Reclamation is one of promotion ways to get perquisites so there are many businessmen in the little or big scale use it. Reclamation is thing, action or media that has goal to commercial, it uses to introducing, persuasion and influence the people to focus in the one of things, services, or someone that can be seen, read and or heard by the people in the some places. Indecisively in giving penalties to the infraction players bring many wild reclamations that without permission detected in every places in Denpasar. Yuridis normative observation is kind of observation that is used. This written will explain how to regulate reclamation organizing in the Denpasar city and onus for some deviations reclamation organizing. The conclusion is unclear act for some infractions in reclamation administrator. giving penalties felony rule will appear chary effect for the doer.